2017
DOI: 10.1007/s00401-017-1681-2
|View full text |Cite
|
Sign up to set email alerts
|

Tau aggregation influences cognition and hippocampal atrophy in the absence of beta-amyloid: a clinico-imaging-pathological study of primary age-related tauopathy (PART)

Abstract: We investigate whether there is any association between the Braak neurofibrillary tangle (NFT) stage and clinical and MRI features in definite primary age related tauopathy (PART). We analysed 52 cases with a Braak NFT tangle stage > 0 and ≤ IV, and a Thal phase of 0 (no beta-amyloid present). Twenty-nine (56%) were female. Median age at death was 88 years (IQR: 82–92 years). Fifteen (29%) were TDP-positive (75% TDP stage I), 16 (31%) had argyrophilic grain disease and three (6%) had alpha-synuclein positive L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
129
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 132 publications
(156 citation statements)
references
References 60 publications
23
129
4
Order By: Relevance
“…However, it is also possible that the relationship between APOE ε4 and TDP-43 is specific to AD. In fact, we did not find any effects of TDP-43 on clinical or neuroimaging outcomes in cognitively normal people with primary age related tauopathy 10 . The findings by Yang and colleagues 7 are also limited to this population and may not necessarily generalize to other populations, particularly since only 34 patients (3%) self-reported their race to be non-white.…”
contrasting
confidence: 71%
“…However, it is also possible that the relationship between APOE ε4 and TDP-43 is specific to AD. In fact, we did not find any effects of TDP-43 on clinical or neuroimaging outcomes in cognitively normal people with primary age related tauopathy 10 . The findings by Yang and colleagues 7 are also limited to this population and may not necessarily generalize to other populations, particularly since only 34 patients (3%) self-reported their race to be non-white.…”
contrasting
confidence: 71%
“…16,17,[27][28][29] These findings are also consistent with laboratory work suggesting that tau is likely the primary mechanism of Aβrelated neurotoxicity, 30 and previous work using other imaging markers of neurodegeneration, [31][32][33][34] suggesting that Aβ pathology in isolation may be insufficient to drive imminent cognitive decline. 36 There have also been two reports of memory decline, using primarily retrospective cognitive trajectories, associated with Linear mixed models were repeated with Aβ treated as a dichotomous variable, and the effect of tau on memory change (Regional tau × Time) was estimated in Aβand Aβ + groups from these models for entorhinal cortex (EC), hippocampus (Hip), and inferior temporal (IT) cortex. These PART studies have reported somewhat variable findings regarding the relationship to cognition, with one recent study finding no association between episodic memory measures and tau pathology, despite substantial hippocampal atrophy, in the setting of low Aβ pathology.…”
Section: Discussionmentioning
confidence: 99%
“…If this is the case, perhaps a longer timeframe than the current study would be necessary to reveal this relationship. Alternatively, it could be that there is little or no relationship between NFT pathology and neurodegeneration in the absence of cerebral amyloid (but note Josephs et al [18] for evidence of increased antemortem MTL atrophy with increasing Braak stage in postmortem PART cases). Finally, it is also possible that 18 F-AV-1451 binds less avidly to more “immature” tangles that are potentially more predominant in PART [19].…”
Section: Discussionmentioning
confidence: 99%